Natural soil biotin application activates soil beneficial microorganisms to improve the thermotolerance of Chinese cabbage - Teng, Zhiyan; Chen, Caizhi; Pan, Kexuan; Liu, Dandan; Yao, Xiangtan; Bai, Songhua; Ni, Jinzhuang; Shao, Yujing; Gu, Zaiyuan; Huang, Li; Chen, Yunwen (Frontiers in Microbiology, 2024)
Chinese cabbage (Brassica campestris L. syn. B. rapa), a widely cultivated leafy vegetable, faces significant challenges in annual production due to high-temperature stress, which adversely affects plant weight and quality. The need for an effective solution to mitigate these impacts is imperative for sustainable horticulture. This study explored the effects of a novel biofertilizer, natural soil biotin (NSB), on Chinese cabbage under high-temperature conditions. NSB, rich in organic matter-degrading enzymes, was applied to assess its impact on crop yield, growth, nutrient use efficiency, product quality, and safety. The study also examined the soil microbial community response to NSB application, particularly the changes in the rhizosphere soil’s fungal population. The application of NSB led to an increase in the abundance of Oleomycetes, which was associated with a decrease in the diversity and abundance of harmful fungi in the rhizosphere soil. This microbial shift promoted the growth of Chinese cabbage, enhancing both plant weight and quality by fostering a more favorable growth environment. Furthermore, NSB was found to reduce lipid peroxidation in Chinese cabbage leaves under high-temperature stress (40°C/30°C, 16 h/8 h, 24 h) by boosting antioxidant enzyme activity and osmoregulatory substance content. The findings suggest that the NSB application offers a promising approach to environmentally friendly cultivation of Chinese cabbage during high-temperature seasons. It contributes to improving the crop’s adaptation to climate change and soil degradation, supporting the development of sustainable agricultural practices. The integration of NSB into agricultural practices presents a viable strategy for enhancing the resilience of Chinese cabbage to high-temperature stress, thereby potentially increasing yield and improving the quality of the produce, which is crucial for the advancement of sustainable horticulture.